Comprehensive Morphometric Analysis of the Foramen Magnum: A Detailed Study with Multiple Parameters - Hussain Saheb Shaik; Indira Thatiparthi; Maruti Ram Annamaraju; Pandit Vinodh Bandela; Haseena Shaik (Current Medical Issues)
Background: The foramen magnum (FM) serves as a critical anatomical conduit between the cranial cavity and vertebral canal, transmitting vital neurovascular structures. Its morphometric characteristics hold significant implications across multiple disciplines, including neurosurgery, forensic anthropology, and evolutionary biology. Despite numerous studies on basic dimensions, comprehensive analyses incorporating multiple parameters remain limited. The present study aimed to conduct a detailed morphometric analysis of the FM using Vernier calipers, measuring and correlating multiple parameters (anteroposterior [AP] diameter, transverse [TV] diameter, area, circumference, and shape index [SI]). In addition, we investigated sexual dimorphism in FM dimensions and classified FM shapes to analyze their distribution. Methodology: A cross-sectional study of 100 dry skulls (60 male and 40 female) was conducted. Precise measurements were obtained using Vernier calipers (0.01 mm precision) and flexible tape. Parameters included AP diameter (basion–opisthion), TV diameter (maximum width), area (π × AP/2 × TV/2), circumference, and SI (TV/AP × 100). Statistical analysis employed SPSS V25 (mean ± standard deviation, Pearson correlation, t-tests; P < 0.05 significant). Results: In the present study, the mean foramen magnum dimensions were as follows: anteroposterior diameter (AP) = 34.8 ± 2.3 mm, transverse diameter (TV) = 29.5 ± 1.9 mm, area = 823.6 ± 45.2 mm², and circumference = 112.4 ± 6.8 mm. A strong positive correlation was observed between AP and TV (r = 0.72, P < 0.001). Sexual dimorphism was significant (P < 0.05) for all parameters except the shape index (SI). The most common shape was oval (65%), followed by round (20%) and irregular (15%). Conclusion: The study provides comprehensive morphometric data demonstrating consistent dimensional relationships through strong parameter correlations, significant sexual dimorphism with larger male dimensions, and predominant oval morphology with notable variability. The findings of the present study enhance understanding of FM anatomy with applications in surgical planning, forensic identification, and anthropological research.